2014
DOI: 10.1103/physrevb.90.115104
|View full text |Cite
|
Sign up to set email alerts
|

Charge and orbital order at head-to-head domain walls inPbTiO3

Abstract: At ferroelectric longitudinal domain walls there is an uncompensated charge, which could form a twodimensional electron gas in the insulator. However, the uncompensated charges can be accommodated by, e.g., defects or localized states that split off from the conduction band. We carried out density functional theory calculations to study these scenarios in PbTiO 3 with and without consideration of strong correlation effects simulated via inclusion of a Hubbard parameter U. The optimized structure and electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…This behavior is very similar to the one observed in charged domain walls in perovskites, e.g., Pb(Ti,Zr)O 3 , where the structural distortions around the longitudinal domain wall are limited to a few unit cells [213]. Also in this case DFT + U calculations have shown that correlation effects have the tendency to localize Ti d electrons ensuring a rather sharp domain wall [214]. At least when 3d transition metal states are involved in the formation of the conduction band, this localization seems to be a general trend in oxides.…”
Section: Dft Calculation and Atomic Simulationssupporting
confidence: 59%
“…This behavior is very similar to the one observed in charged domain walls in perovskites, e.g., Pb(Ti,Zr)O 3 , where the structural distortions around the longitudinal domain wall are limited to a few unit cells [213]. Also in this case DFT + U calculations have shown that correlation effects have the tendency to localize Ti d electrons ensuring a rather sharp domain wall [214]. At least when 3d transition metal states are involved in the formation of the conduction band, this localization seems to be a general trend in oxides.…”
Section: Dft Calculation and Atomic Simulationssupporting
confidence: 59%
“…The gap level close to the valence band originates from occupied Fe d orbitals oriented along Fe-O bonds being pushed energetically upward, while the one at higher energy is from the Fe d orbitals that are directed away from Fe-O bonds and are occupied by the excess electron. The same electron trapping (small electron polaron) has been discussed in the case of charged domain walls in ErMnO 3 [18] and PbTiO 3 [19]. In the case of BiFeO 3 , we could have actually expected electron trapping instead of delocalized metallic behavior because the d states of Fe at the bottom of the conduction band are relatively isolated both in space and in energy.…”
supporting
confidence: 64%
“…Due to the discrete electronic states resulting from the electric gas, signatures of resonant tunneling were observed, giving rise to quantum oscillations of the tunneling conductance. On the theoretical side, it has been shown that a head-to-head domain-wall structure can be created in a ferroelectric PbTiO 3 layer through the artificial electron doping at the interface [48], and such a domain wall can lead to spindependent resonant tunneling in a MFTJ [49]. These results demonstrate that a ferroelectric domain wall can be used as the controlling element of the transport properties of a FTJ [50].…”
Section: Introductionmentioning
confidence: 92%